The role of logical thinking in mother tongue lessons - Akmaldinova Feruza Inoqjon qizi (Peerian Journals Publishing, 2023)
logical thinking plays an important role in language development and communication. It is a necessary cognitive process that allows individuals to communicate, reason and effectively express their thoughts and ideas. In this article, we will study the importance of logical thinking in language and how it contributes to effective communication.
Keywords: logical thinking; personality reading